2019
DOI: 10.1109/taffc.2017.2699633
|View full text |Cite
|
Sign up to set email alerts
|

New Methods for Stress Assessment and Monitoring at the Workplace

Abstract: Abstract-The topic of stress is nowadays a very important one, not only in research but on social life in general. People are increasingly aware of this problem and its consequences at several levels: health, social life, work, quality of life, etc. This resulted in a significant increase in the search for devices and applications to measure and manage stress in real-time. Recent technological and scientific evolution fosters this interest with the development of new methods and approaches. In this paper we su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 79 publications
(77 reference statements)
1
24
0
1
Order By: Relevance
“…Another challenge is how to deploy the stress prediction models. The recent reviews on stress recognition [1] 3 https://www.empatica.com/research/e4/ [3] unanimously concluded that due to the physiological difference in how people react to stress, a stress monitoring system should adapt to every individual's physiological needs. The simple, and likely, the most accurate approach is to deploy each person's stress prediction model as a web service (e.g., Representational State Transfer (REST) web service) that can be consumed to predict the person's stress.…”
Section: S T R E S S M O N I T O R I N G I N O F F I C E Smentioning
confidence: 99%
See 2 more Smart Citations
“…Another challenge is how to deploy the stress prediction models. The recent reviews on stress recognition [1] 3 https://www.empatica.com/research/e4/ [3] unanimously concluded that due to the physiological difference in how people react to stress, a stress monitoring system should adapt to every individual's physiological needs. The simple, and likely, the most accurate approach is to deploy each person's stress prediction model as a web service (e.g., Representational State Transfer (REST) web service) that can be consumed to predict the person's stress.…”
Section: S T R E S S M O N I T O R I N G I N O F F I C E Smentioning
confidence: 99%
“…Moreover, in the case of physiological evaluations, people are reluctant to reveal their work stress honestly [15]. Luckily, stress spawns detectable physiological, psychological, and behavioral changes that can be used for automatic stress recognition [1] [5]. For example, acute stress decreases a person's Heart Rate Variability (HRV) and his parasympathetic activation [16].…”
Section: Introduction O C U Pa T I O N a L Stress Is Well-mentioning
confidence: 99%
See 1 more Smart Citation
“…The following two sections will briefly present two pilot studies based on the creation of such scenarios. Our work was also driven towards considering stress assessment at the workplace [18].…”
Section: Background Work In Gsdmentioning
confidence: 99%
“…Next, participants were required to select from a list of eighteen (18) topics which ones should be presented. Finally, participants should identify the team member who should present each of the selected topics.…”
Section: Investigating Gse Project Managementmentioning
confidence: 99%